HUSSERL AND CULTURAL RELATIVISM - AGUIRRE GARCÍA, JUAN CARLOS (Disertaciones, 2012)
Many times, Husserl’s Phenomenology is looked as prone to cultural relativism. The aim of this paper is to challenge that interpretation. In order to achieve this aim, I will show the critiques that Husserl makes to the Historicism (especially in Logos, a phenomenological journal). Then, I will approach to the Carr’s interpretation of Husserl in which he is charged of cultural relativism. Finally, I will face that interpretation and I will show how from Husserl work is not deduced such relativism which is charged.